Mathematics Anxiety: An Intergenerational Approach - Vanbinst, Kiran; Bellon, Elien; Dowker, Ann (Frontiers in Psychology, 2020)
This study investigated mathematics anxiety from an intergenerational perspective, by investigating data on 172 primary school children and both their biological parents. This family dataset (n = 516) allowed us to not only replicate previous findings per generation, but, importantly, to explore intergenerational correlations. We found a significant negative association between sixth graders’ arithmetical performance and their mathematics anxiety. Gender differences occurred in each generation: females were more anxious than males about mathematics. Interestingly, these gender differences were not found in actual arithmetical performance. Analyses of our intergenerational data revealed that children’s mathematics anxiety was significantly associated with their mothers’ mathematics anxiety and both their mothers’ and fathers’ educational level. Regression analyses revealed that the significance level of mothers’ mathematics anxiety became borderline when considering mathematics anxiety and educational level of both parents simultaneously. Interestingly, mathematics anxiety as well as educational level of both biological parents was associated, suggesting that mathematics anxiety results from a complex entanglement of nature and nurture. Current intergenerational data suggest a complex familial basis of mathematics anxiety and indicate that the investigation of parental levels of education and mathematics anxiety contributes to the understanding of individual differences in children’s arithmetic performance.